Have We Forgotten Auditory Sensory Memory? Retention Intervals in Studies of Nonverbal Auditory Working Memory - Nees, Michael A. (Frontiers in Psychology, 2016)
Researchers have shown increased interest in mechanisms of working memory for nonverbal sounds such as music and environmental sounds. These studies often have used two-stimulus comparison tasks: two sounds separated by a brief retention interval (often 3 to 5 s) are compared, and a “same” or “different” judgment is recorded. Researchers seem to have assumed that sensory memory has a negligible impact on performance in auditory two-stimulus comparison tasks. This assumption is examined in detail in this comment. According to seminal texts and recent research reports, sensory memory persists in parallel with working memory for a period of time following hearing a stimulus and can influence behavioral responses on memory tasks. Unlike verbal working memory studies that use serial recall tasks, research paradigms for exploring nonverbal working memory—especially two-stimulus comparison tasks—may not be differentiating working memory from sensory memory processes in analyses of behavioral responses, because retention interval durations have not excluded the possibility that the sensory memory trace drives task performance. This conflation of different constructs may be one contributor to discrepant research findings and the resulting proliferation of theoretical conjectures regarding mechanisms of working memory for nonverbal sounds.